2019
DOI: 10.1016/j.dark.2018.100253
|View full text |Cite
|
Sign up to set email alerts
|

Hořava–Lifshitz cosmology in light of new data

Abstract: We present new observational constraints on Lorentz violating Hořava-Lifshitz cosmological scenarios using an updated cosmological data set from Cosmic Microwave Background (Planck CMB), expansion rates of elliptical and lenticular galaxies, JLA compilation (Joint Light-Curve Analysis) data for Type Ia supernovae (SneIa), Baryon Acoustic Oscillations (BAO) and priors on the Hubble parameter with an alternative parametrisation of the equations. Unlike in other approaches we consider the curvature parameter Ω k … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 75 publications
(171 reference statements)
0
29
0
Order By: Relevance
“…a e-mail: anpaliat@phys.uoa.gr b e-mail: genly.leon@ucn.cl (corresponding author) c e-mail: J.D. Barrow@damtp.cam.ac.uk Lifshitz theory using some of the recent cosmological data can be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…a e-mail: anpaliat@phys.uoa.gr b e-mail: genly.leon@ucn.cl (corresponding author) c e-mail: J.D. Barrow@damtp.cam.ac.uk Lifshitz theory using some of the recent cosmological data can be found in [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the review [69] are discussed some recent developments of the HL theory: (i) universal horizons, black holes and their thermodynamics; (ii) non-relativistic gauge/gravity duality; and (iii) quantization of the theory. In the reference [70] was tested HL cosmological scenarios against the new observational constraints: an updated cosmological data set from Cosmic Microwave Background (Planck CMB), expansion rates of elliptical and lenticular galaxies, JLA compilation (Joint Light-Curve Analysis) data for Type Ia supernovae (SneIa), Baryon Acoustic Oscillations (BAO) and priors on the Hubble parameter with an alternative parametrization of the equations. The authors considered the curvature parameter as a free parameter in the analysis, and they found that the detailed-balance scenario exhibits positive spatial curvature to more than 3σ , whereas for further theory generalizations it was found evidence for positive spatial curvature at 1σ .…”
Section: Introductionmentioning
confidence: 99%
“…Although the detailed-balance condition leads to a succinct action, there is an ongoing debate in the literature whether this formulation is too restrictive. In fact, there are a number of problems with the detailed-balance scenario, such as instabilities, strong coupling at low energies, as well as problems with the value of the cosmological constant [9,11,37,44]. As such, we choose to focus our efforts on the so-called beyond detailed balance scenario [21,43,[46][47][48], where it is possible to include more terms in the potential V. Then, using the FLRW line element and populating the Universe with the canonical matter fields, the first Friedmann equation can be written:…”
Section: Hořava-lifshitz Gravitymentioning
confidence: 99%